2013
DOI: 10.1007/s00264-012-1745-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a cervical spine cage to reconstruct malunited fibular fractures

Abstract: Purpose Anatomical reduction and fixation of unstable ankle fractures is necessary to prevent post-traumatic arthritis. Malunion of the distal fibula in unstable ankle fractures can lead to late degenerative changes of the ankle. Late reconstruction of the ankle can improve its function and postpone the need for ankle fusion or replacement. Methods We discuss three patients who presented with fibular malunion. All developed medial gutter opening, syndesmotic widening, and lateral shift and/or talar tilt. Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Transverse osteotomy with bone graft and plate fixation has been reported as a successful treatment for patients with fibular shortening. 1,9,18 Offierski et al 6 described good clinical results in 8 of 11 patients treated in this manner. Weber and Simpson 18 reported that among 23 patients treated with distal fibular lengthening osteotomies, 17 experienced good to excellent results at an average followup of 11 years.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Transverse osteotomy with bone graft and plate fixation has been reported as a successful treatment for patients with fibular shortening. 1,9,18 Offierski et al 6 described good clinical results in 8 of 11 patients treated in this manner. Weber and Simpson 18 reported that among 23 patients treated with distal fibular lengthening osteotomies, 17 experienced good to excellent results at an average followup of 11 years.…”
Section: Discussionmentioning
confidence: 90%
“…8,15 Several techniques have been introduced for lateral malleolar reconstruction, including transverse, oblique, and Z-osteotomy. 1,9,10,18,19 Transverse osteotomy with bone grafting and internal fixation has been shown to effectively treat fibular shortening. 1,9,18 An AO distractor can be used to distract the osteotomy and thus achieve the correct fibular length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The article published by Visser et al (2017) describes the completion of a fibular lengthening using a frozen allogeneic graft taken from the femoral head, which avoids the morbidity of the donor area itself [18]. In this respect, the paper by Brin et al (2013) [19] is also of interest; it presents the advantage of using cervical spine cage type devices, with excellent results as an alternative to the bone graft habitually used until now.…”
Section: Discussionmentioning
confidence: 99%